Signatures of Radiation‐Induced Stress and Putative Selection on Immune Targets in Chornobyl Wolves - Cara N. Love; Stacey L. Lance; Thomas G. Hinton; Nicolas Rochette; James C. Beasley; Dmitry Shamovich; Michael E. Byrne; Brian Nadel; Sarah C. Webster; Shane C. Campbell‐Staton (Molecular Ecology, 2026)
Investigating the physiological and evolutionary consequences of contaminant exposure in wild populations is critical for understanding long‐term ecological impacts of anthropogenic change. However, how and why species persist, even thrive, in highly contaminated regions in the absence of humans remains a topic of much debate. We examined the regulatory and genomic impacts of multigenerational chronic radiation exposure to grey wolves ( Canis lupus ) within the Chornobyl Exclusion Zone. Wolves within the exclusion zone are at an estimated seven times greater density than surrounding preserves, despite lack of physical barriers to dispersal and chronic exposure to elevated radiation dose. Demographic analyses of genetic variation and home range modelling further suggest that ecological factors may support the wolf population within the exclusion zone. Wolves within Chornobyl exhibit altered leukocyte composition and regulatory signatures within the blood transcriptome that support significant alterations to metabolic and immune response pathways, particularly those influential in DNA damage response indicating radiation‐induced immune modulation. Selection scans across genes within the blood transcriptome revealed multiple regions of accelerated Chornobyl‐specific divergence at loci with known roles in immunity and response to oncogenesis. Together, these data provide evidence that chronic exposure to ionising radiation may be a significant source of ongoing natural selection in an apex predator after a single contamination event, highlighting multigenerational impacts beyond initial exposure. Further, these results highlight the potential contributions of natural selection to species persistence and proliferation in highly contaminated ecosystems.